Economic growth in the 1990s : learning from a decade of reform - Zagha, Roberto; Nankani, Gobind T. (Washington, D.C. : World Bank, 2005)
This book is part of a larger effort undertaken by the World Bank to understand the development experience of the 1990s, an extraordinary eventful decade. Each of the project's three volumes serves a different purpose. Development Challenges in the 1990s: Leading Policymakers Speak from Experience offers insights on the practical concerns faced by policymakers, while At the Frontlines of Development: Reflections from the World Bank considers the operational implications of the decade for the World Bank as an institution. This volume, Economic Growth in the 1990s: Learning from a Decade of Refo
This report was prepared by a team led by Roberto Zagha, under the general direction of Gobind Nankani.
Includes bibliographical references (p. 331-356) and index.
eng
Keywords: Economic stabilization -- Developing countries; Privatization -- Developing countries